Pelatihan dan Pendampingan Penyusunan Perangkat Pembelajaran Berbasis Deep Learning untuk Meningkatkan Kinerja Guru di MTs Al Maarif Tulungagung - Indah Komsiyah; Evy Ramadina (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This community service research aims to improve teacher performance at MTs Al Maarif Tulungagung through training and mentoring in developing deep learning-based learning tools by integrating mindful, meaningful, and joyful concepts. This PKM is implemented using the Asset-Based Community Development (ABCD) Method, which focuses on utilizing and optimizing teacher potential and madrasah resources as the main assets. The program is implemented in two stages: intensive training on the concept and framework of Deep Learning, followed by practical mentoring in developing Teaching Modules based on this approach. The results of the activity showed a significant increase in teacher competency. After the program, all teachers successfully completed the development of Deep Learning-based Teaching Modules. In general, this community service activity has succeeded in empowering teachers. The resulting Teaching Modules have the potential to improve the quality of learning by facilitating more meaningful, conscious, and enjoyable learning experiences for students, which will ultimately improve teachers' professional performance independently and sustainably.